하천 및 호소 수질관리를 위한 용존 자연유기물질 형광특성 분석 - 허진(Jin Hur); 신재기(Jae Ki Shin); 박성원(Sung Won Park) (Daehan hwan'gyeong gonghag hoeji, 2006)
Fluorescence measurements of dissolved organic matter(DOM) have the superior advantages over other analysis tools for applying to water quality management. They are simple and fast and require minimal pretreatment of samples. Fluorescence index($F_{450}/F_{500}$), synchronous spectra, and fluorescence excitation-emission matrices(EEM) of various DOM samples were investigated to discriminate autochthonous/allochthonous composition, protein-like fluorescence, fulvic-like fluorescence, humic-like fluorescence, terestrial humic-like fluorescence by comparing among the real DOM samples of different origins with the help of literature. The samples used included standard purified DOM, lake, river and wastewater treatment effluent. The relative distribution of various DOM composition was derived from the ratios of each fluorescence region. The results were very consistent with those expected from the sample properties. Allochthonous and terrestrial humic-like fluorescence were more prominent in the samples with abundant soil-derived DOM components. In addition, the protein-like fluorescence property was more pronounced in the samples where strong algal or microbial activities were expected. It was also shown that the ratio of protein-like/terrestrial humic-like fluorescence obtained from synchronous spectrum and fluorescence EEM could be used as an indicator for the evaluation of wastewater treatment on the downstream water quality of rivers and for the prediction of the degree of algal/microbial activities in lakes. It is expected that the results of this study will provide the basic information to develop the future water quality management techniques using DOM fluorescence measurements. 형광측정법은 자연유기물질을 간편하고 신속하게 분석함으로써 타 분석법에 비해 현장에서 실시간으로 수질관리에 활용할 수 있는 월등한 장점을 가지고 있다. 본 연구에서는 표준자연유기물질, 호소수 및 하천수 등 다양한 시료의 형광지표($F_{450}/F_{500}$), synchronous 스펙트럼, 형광 EEM(excitation-emission matrix)을 조사하고 시료 간 상호비교를 통해 자체생성/외부생성 유기물, 단백질계, 펄빅산계, 휴믹산계, 육질성 휴믹산계 형광특성 영역을 구분하였다. 또한 각 영역간의 형광세기 비를 이용하여 다양한 유기물 성분의 상대적인 분포를 파악하였다. 각 시료에서 얻어진 형광특성 및 형광세기 비는 시료의 수질 특징에서 예상되는 결과와 잘 일치하였다. 자연유기물의 생성지가 육지성일수록 외부생성 유기물 및 육질성 휴믹산계 형광특징이 더 크게 나타났고 하수 처리수의 영향을 받거나 조류 및 미생물 활동이 활발한 지점에서는 단백질계 형광특성이 뚜렷하게 나타났다. 특히, synchronous 형광스펙트럼이나 형광 EEM에서 얻어지는 단백질계/육질성 휴믹산계 형광세기 비는 도심지 하천의 경우 하수종말처리장 방류수 영향을 평가하는 지표로, 또한 호수의 경우 조류 및 미생물 활동 정도를 예측하는 지시자로서 사용될 수 있음을 보여 주었다. 본 연구는 현장시료를 사용한 자연유기물질 형광분석법 및 그 해석에 대한 기초자료를 제시하였으며 이 연구결과는 향후 유기물 성분분포 파악이 필요한 수질관리 분야에서 유용하게 사용될 수 있을 것으로 기대한다.